Testing the Physical Activity Self-Definition Model among low-active adults participating in a physical activity intervention. (November 2021) - Morgan, Tamara L.; Semenchuk, Brittany N.; Duhamel, Todd A.; Blanchard, Chris; Sweet, Shane N.; Kent, David; Meade, Laura; Whaley, Diane; Strachan, Shaelyn M.
Abstract: Seeing oneself as a physically active person is one of the strongest predictors of physical activity behaviour and self-regulatory strategies. Determining whether and how physical activity self-perceptions can be stimulated may help low-active individuals who do not see themselves as a physically active person become more active. Cross-sectional research has tested the Physical Activity Self-Definition (PASD) model among active samples; longitudinal studies among low-active adults have yet to be done. The purpose of this study was to test the predictive power of the PASD model among low-active adults over a 16-week physical activity intervention. Participants completed surveys of validated questionnaires in-person at baseline (pre-intervention) and at 16-weeks (end of intervention) at one of two primary care facilities. The final sample included 119 low-active adults. Partial least squares-structural equation modeling indicated that the original model had small-medium predictive power ( Q 2 = 0.22; SRMR = 0.13 [0.05, 0.07]; RMSE = 1.13; MAE = 0.9; BIC = 1348.40). Two paths were added in the revised model (perceived wanting—PASD; perceived ability—perceived commitment), which explained an additional 4% and 5% of the variance in perceived commitment ( R 2 = 0.62 [0.48, 0.72]) and PASD ( R 2 = 0.74 [0.64, 0.80]; all p 's < 0.001), respectively. The revised model had medium predictive power ( Q 2 = 0.25; SRMR = 0.11 [0.05, 0.06]; RMSE = 1.1; MAE = 0.87; BIC = 1332.84) All path coefficients remained positive and significant at p ≤ .001. Among low-active adults, perceived wanting and perceived ability may be more salient when engaging in physical activity and regarding themselves as a physically active person. Findings may support practitioners and health care professionals in designing physical activity interventions to foster PASD among low-active adult populations. Highlights: The Physical Activity Self-Definition model was examined among low-active adults. Adding two pathways improved the model's predictive power in our sample. Valuing physical activity may help low-active adults view themselves as active. Feeling skilled at physical activity may help low-active adults feel committed.